2003
DOI: 10.1007/s007740300006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of four bone mineral density candidate genes in Chinese populations and comparison with other populations of different ethnicity

Abstract: Studies on polymorphisms of candidate genes and their association with bone mineral density (BMD) have been reported in many populations, but few have been reported in Chinese populations. We investigated polymorphisms of the following five commonly used markers of four prominent BMD candidate genes with the purpose of identifying useful genetic markers for osteoporosis genetic research in Chinese: the Sp1 and RsaI polymorphisms of the collagen type 1 alpha l (Col1a1) gene, the -174G/C promoter polymorphism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…Genotypes of all subjects in the 401 nuclear families were determined using PCR-RFLP reaction protocols as described by Lei et al (2003). The genotypes were designated as PP, Pp, pp for ERPvuII, XX, Xx, xx for ER-XbaI, and AA, Aa, aa for VDR-ApaI.…”
Section: Genotypingmentioning
confidence: 99%
“…Genotypes of all subjects in the 401 nuclear families were determined using PCR-RFLP reaction protocols as described by Lei et al (2003). The genotypes were designated as PP, Pp, pp for ERPvuII, XX, Xx, xx for ER-XbaI, and AA, Aa, aa for VDR-ApaI.…”
Section: Genotypingmentioning
confidence: 99%
“…For example, some studies have found that the Sp1 polymorphism in the COL1A1 gene contributes to susceptibility to vertebral fracture or BMD [12,15,16,18] , but other studies have reported that there is no such association [20,21] . These discordant findings may be due to the inclusion of study subjects from populations with different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…These discordant findings may be due to the inclusion of study subjects from populations with different ethnicities. Due to the lack of the Sp1 polymorphism in Chinese women [20,21] , this SNP was not evaluated in the present study. Few studies have investigated the association among other SNPs (excluding the Sp1 polymorphism) in COL1A1 and osteoporotic fracture or BMD [16,17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not examine the Sp1 polymorphism that is the most commonly studied marker at COLIA1, because it is not polymorphic in East Asians (Lei et al 2003).…”
Section: Discussionmentioning
confidence: 99%